IMPROVEMENT OF PHYSICAL FITNESS LEARNING RESULT THROUGH METHOD PLAY OF CLASS VIII STUDENTS AT PUBLIC JUNIOR HIGH SCHOOL 5 PALLANGGA IN GOWA DISTRICT - Irfan Irfan; Rahmanul Hakim (Program Pascasarjana Universitas Negeri Jakarta, 2018)
The purpose of this study is to describe efforts to improve physical fitness learning outcomes through the method of playing on students of class VIII public junior high school 5 Pallangga Gowa District. Approach in this research is qualitative descriptive approach with class action research type. The implementation of this research is focused on two variables, namely the method of play and physical fitness learning outcomes. This research was conducted in public junior high school 5 Pallangga Gowa Regency with research subjects of VIII students amounting to 40 people. Data collection techniques used are observation, test and documentation. Data analysis techniques used are qualitative and quantitative descriptions. Based on the results of the study concluded that learning through the application of play methods can improve physical fitness learning outcomes in grade VIII students. From the analysis result obtained significant improvement from cycle I and cycle II. The result of physical fitness learning in cycle I in the finished category is 37.5% with the number of students 15 people whereas in cycle II there is an increase in the percentage of student learning outcomes in the complete category of 95% with 38 students complete. Keywords: Learning Outcomes, Physical Fitness, Playing Methods